IMPLEMENTATION OF MEDIUM VOLTAGE AUTOMATIC CHANGE OVER (ACO-MV) DEVICE AS POWER OUTAGE REDUCTION FOR PREMIUM CUSTOMERS AT PT PLN (PERSERO) UP3 KRAMAT JATI - Oracle Bramantyo Wardhana; Rahmat Hidayat (TEKNOKOM, 2023)
This qualitative research analyzes the implementation of the ACO-MV device in reducing power outages. The study aims to understand the experiences, perspectives, and impacts of the ACO-MV device on stakeholders, including premium customers, businesses, and industries. Using a qualitative approach, in-depth interviews are conducted with key stakeholders, such as PT PLN (PERSERO) UP3 Kramat Jati representatives, premium customers, and business owners. These interviews provide insights into their experiences and perspectives regarding the ACO-MV device. Observational studies and document analysis supplement the interview data, providing a comprehensive understanding of outage incidents, device operation, and maintenance procedures. Thematic analysis is employed to identify recurring themes, patterns, and insights related to the effectiveness of the ACO-MV device in reducing power outages and its impact on stakeholders. The research findings contribute to a deeper understanding of the qualitative aspects of the ACO-MV device's implementation, informing decision-making and potential improvements in its design, operation, and maintenance. The framework and dataset utilized in this study offer a robust foundation for analyzing stakeholder perspectives and experiences. This research helps advance the understanding of the ACO-MV device's impact on power outage reduction and supports informed decision-making processes.